Migrants from Afghanistan on the Swedish Labour Market - Fredrik W. Andersson; Eskil Wadensjö (Institute of Labor Economics (IZA), 2024)
The number of immigrants to Sweden has increased significantly in the last two decades. In 1990, 9 percent of the population was born abroad. Just over 60 percent of them were born in Finland, Norway and Denmark. Thirty years later, the corresponding figure of foreign born is 20 percent. The composition has also changed. Many have arrived as refugees mainly from countries outside Europe until the great wave of refugees from Ukraine in 2022. We concentrate in this article on one group, those who have come from Afghanistan, and examined how it has gone for them to establish themselves in the labour market in Sweden.
Keywords: F22; J15; J21; J60; J61; 330; Swedish labour market; employment; migrants; Afghanistan